Pengembangan Antarmuka Mantuls.com Berbasis Perangkat Bergerak Menggunakan Metode Goal-Directed Design (GDD) - Bhanio Gemilang Putakaz; Retno Indah Rokhmawati; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Mantuls.com is a web-based application that serves to help Event Hunter to get competition information easily, up to date, and with a choice of well-curated information. The Goal Directed Design method can produce an application design that is suitable for the user's goals. In applying the Goal Directed Design (GDD) method, it has six stages, the first stage is research to get problems and solutions that are desired by users and stakeholders. The second stage is modeling that produces persona and describes the user or stakeholder, the third stage is the requirement that will produce the needs of the user, the fourth stage is a framework that produces a designed interface framework, then the fifth stage is a refinement that will produce high fidelity prototypes it is ready to be tested, and the last stage is support that performs testing and analysis of test results on the prototype that has been made. The final evaluation here uses the System Usability Scale (SUS) Questionnaire. After developing using the Goal-Directed Design (GDD) method. The average value of the value of the System Usability Scale is obtained (value), with Acceptability values ​​above 73 and also grade scales with category b, and Adjective Rating with Excellent and Percentile Rank categories categorized as group A.